Writing Task Complexity, Task Condition and the Efficacy of Feedback - Esmaeil Ghaderi; Afsar Rouhi; Amir Reza Nemat Tabrizi; Manoochehr Jafarigohar; Fatemeh Hemmati (National Research University Higher School of Economics, 2022)
Background. Task-based language teaching (TBLT) is still attracting considerable interest from second language teachers and researchers, partly due to unresolved issues of task sequencing and task complexity. Moreover, in spite of burgeoning attention to writing at the present stage of evolution of TBLT, the interaction of task complexity and corrective feedback in writing performance of language learners has not been explored well. Purpose. To fill in this research gap, the present study aimed to explore the role of task complexity and task condition in learners' gain from corrective feedback in second language writing. Methods. A pretest-immediate posttest-delayed posttest design was adopted in this study. The participants of the study were 114 English as foreign language learners, randomly assigned to one of the five groups: four experimental groups and a control group. The four experimental groups differed in (a) whether they carried out the simple or complex version of a task (b) whether they did the writing task individually or collaboratively. They received feedback on their writing in three treatment sessions. Results. Statistical analyses revealed that task condition played a larger role than task complexity in the linguistic performance of language learners who received feedback on their writing. Conclusion. The findings add support to the view that selecting appropriate levels of task complexity and suitable task implementation conditions alongside providing corrective feedback enhances the different dimensions of the written performance of language learners.